15th AIAA Computational Fluid Dynamics Conference 2001
DOI: 10.2514/6.2001-2773
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of a synthetic jet with a flat plate boundary layer

Abstract: The interaction of a modeled synthetic jet with a flat plate boundary layer is investigated numerically using an incompressible Navier-Stokes solver. The diaphragm is modeled in a realistic manner as a moving boundary in an effort to accurately compute the flow inside the jet cavity. The primary focus of the current study is on describing the dynamics of the synthetic jet in the presence of external crossflow. A systematic parametric study has been carried out where the diaphragm amplitude, external flow Reyno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
62
0
3

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(68 citation statements)
references
References 14 publications
3
62
0
3
Order By: Relevance
“…Chen et al [4] and Davis and Glezer [6] have presented the mixing enhancement for the active control of separation and turbulence in the boundary layer (see also Smith and Glezer [15], and Crook et al [5]). Mittal et al [12] studied the performance of a synthetic jet actuator, based on a number of geometrical, structural and flow parameters. Amitay et al [1] demonstrated the usage of synthetic jets in delaying separation.…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [4] and Davis and Glezer [6] have presented the mixing enhancement for the active control of separation and turbulence in the boundary layer (see also Smith and Glezer [15], and Crook et al [5]). Mittal et al [12] studied the performance of a synthetic jet actuator, based on a number of geometrical, structural and flow parameters. Amitay et al [1] demonstrated the usage of synthetic jets in delaying separation.…”
Section: Introductionmentioning
confidence: 99%
“…In developing synthetic jet actuators (SJAs) for active flow control, extensive work has been conducted on numerical modeling of the synthetic jet generated in a quiescent external flow condition (in the absence of a cross flow) [ [11], [14], [17], [25]]. In this numerical modeling, the neighborhood of the jet exit was simulated.…”
Section: Introductionmentioning
confidence: 99%
“…They also investigated various jets, laminar and turbulent, pulsed and steady, and achieved very good agreement between the numerical simulation and the experimental measurement. The models in [[14], [17], [25]] included the flow behavior in the cavity of the actuator and simulated not only the jets generated but also the compression/intake and expansion/discharging processes in the cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, synthetic jets have been found to achieve similar effectiveness to steady blowing or suction with considerably smaller momentum (and hence lower energy inputs). 1 The problem of synthetic jet flow in a turbulent boundary layer has been studied both experimentally (see, for example [2][3][4][5] ) and computationally (see, for example [6][7][8][9][10][11] ). Earlier numerical work by Rizzetta et al 12 for synthetic jets into quiescent flow demonstrated that accounting for the internal actuator geometry was important because it affected the jet profiles at the exit.…”
Section: Introductionmentioning
confidence: 99%